The Features of Theatrical Life in Hungary: The Legal and Financial Basis - Romanova, Olga; Khaunina, Ekaterina (Slavica, 2018)
The present study is concerned with the Hungarian theatre system. In the first part generalquestions connected with the existing model of theatrical activity are treated. This isfollowed by an analytical review of modern Hungarian cultural legislation, in which specialattention is paid to the structure and content of Law XCIX / 2008 “On the support and rulesof employment in organizations of performing arts”. Then all the existing present-day modelsof direct and indirect financial support of theatrical organizations are considered. Since theHungarian and Russian theatre systems have some similar characteristics, the final part isdevoted to possible partial adoption of Hungarian experience with a view to developing theinstitutions for the additional funding of Russian theatres.